PAS stakeholders & activities to achieve alignment - Monique Arkesteijn (A+BE: Architecture and the Built Environment)
PAS consists of three main components; steps, stakeholders & activities, and mathematical models, as explained in chapter 4. In this chapter, the stakeholders & activities are the focal point (see Figure 6.1). By explaining the interactive design process in detail, the reader understands how the stakeholders perform the activities to achieve alignment between the organization and the corporate real estate portfolio.